2019
DOI: 10.3390/jmmp3010006
|View full text |Cite
|
Sign up to set email alerts
|

Full-Density Fused Deposition Modeling Dimensional Error as a Function of Raster Angle and Build Orientation: Large Dataset for Eleven Materials

Abstract: This paper describes the collection of a large dataset (6930 measurements) on dimensional error in the fused deposition modeling (FDM) additive manufacturing process for full-density parts. Three different print orientations were studied, as well as seven raster angles ( 0 ∘ , 15 ∘ , 30 ∘ , 45 ∘ , 60 ∘ , 75 ∘ , and 90 ∘ ) for the rectilinear infill pattern. All measurements were replicated ten times on ten different samples to ensure a comprehensive dataset. Elev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 43 publications
(63 reference statements)
0
17
1
Order By: Relevance
“…In the present work, dimensional error values of up to 2.6% are obtained. Messimer et al [42] reported slightly higher values of up to 3% for high-temperature polylactic acid (HTPLA).…”
Section: Regression Model For Dimensional Errormentioning
confidence: 99%
“…In the present work, dimensional error values of up to 2.6% are obtained. Messimer et al [42] reported slightly higher values of up to 3% for high-temperature polylactic acid (HTPLA).…”
Section: Regression Model For Dimensional Errormentioning
confidence: 99%
“…The authors attributed this decrement due to variability in the raster. Another important aspect to consider when dealing with geometrical issues is the dimensional error to evaluate the manufacturing accuracy [53].…”
Section: Experimental Characterization Of Mechanical Propertiesmentioning
confidence: 99%
“…Additive manufacturing or 3D printing techniques allow small batches of parts to be produced directly, economically, and flexibly [1]. There are different additive manufacturing techniques; however, fused deposition modeling (FDM) printers are the most extended due to their low cost and the wide variety of materials that can be used [2,3,4].…”
Section: Introductionmentioning
confidence: 99%